Effect of an early supervised rehabilitation programme compared with home-based exercise after temporomandibular joint condylar discopexy: a randomized controlled trial. Issue 3 (March 2017) - Capan, N.; Esmaeilzadeh, S.; Karan, A.; Dıracoglu, D.; Emekli, U.; Yıldız, A.; Baskent, A.; Aksoy, C.
Abstract: The goal of rehabilitation after temporomandibular joint (TMJ) surgery is to achieve a normal range of motion. The aim of this study was to compare the impact of a comprehensive and early supervised rehabilitation programme with home-based exercise after TMJ condylar discopexy. Patients diagnosed with disc displacement without reduction were randomized to the study and control groups. After baseline assessments, the same surgical condylar discopexy procedure was applied to both groups. Following surgery, the study group patients underwent a supervised exercise programme conducted by a physiotherapist in the outpatient clinic. This comprised 30-min sessions 3 days per week for 8 weeks in the hospital. The control group patients performed the same exercise programme at home. Maximum mouth opening (MMO), protrusion, and right and left lateral movements were measured. Based on the results, the supervised rehabilitation programme yielded significantly better outcomes for pain at rest and with activity, MMO, and protrusion compared with the home-based exercise programme. Also certain parameters of quality of life improved significantly in the study group. In conclusion, exercise therapy is the cornerstone of rehabilitation of the TMJ, and a supervised rehabilitation programme after TMJ surgery is effective in improving functional parameters.